Types of Childhood Maltreatment, Neighborhoods, and Intimate Partner Violence: An Ecological Perspective - Yohros, Alexis (Victims & offenders, 2021)
Studies have begun to recognize the multilevel and complex nature of intimate partner violence. Yet, only a small number of studies have looked at the interactive relationship between proximal and community risk factors, including how childhood factors and neighborhood characteristics interact to shape partner violence outcomes. Through an ecological framework, the current study examines the direct and interactive effects of various types of childhood maltreatment and neighborhood context on intimate partner violence. Using data from the National Longitudinal Study of Adolescent to Adult Health, this research analyzes whether the effects of childhood victimization on partner violence vary across neighborhood context while considering the role of gender and examining differences in victimization and perpetration. Results from multilevel logistic regressions find that for women, higher levels of residential instability and racial/ethnic heterogeneity increase the effect of maltreatment on intimate partner violence. These effects vary across types of maltreatment and partner violence outcomes. The findings highlight the importance of considering community context in revictimization experiences.